SIFAT ANTIOKSIDAN PADA VIRGIN COCONUT OIL (VCO) JAHE - Martina Andriyani (Caraka Tani: Journal of Sustainable Agriculture, 2008)
Virgin Coconut Oil (VCO) representing oil which extracted from coconut kernel without hot process but with ferment technique nor with enzyme owning certain typical aroma which less taken a fancy by consumer from facet acceptance. Addition of ginger at VCO cause certain flavor so that ginger VCO more able to be accepted by consumers. One of the ginger component is oleoresin representing resin mixture and resin atsiri oil in the oleoresin consist of active component in the form of fenol like gingerol, shogaol, and zingerone; that give hot feel while ginger atsiri oil component are a-pinene, camphene, phellendrene, mycene, cineol, methythe-ptenone, borneol, linalool, citral, and Ca-Aldehid C10, b-zingiberone a-dan, a-curcumene, farnesene, sesquiterpene that give ginger aroma characteristic. Used of ginger in so many mace ingredient, traditional refreshments give flavor and ginger typical aroma and to be recognized, and also is enough taken a fancy by Indonesia society. Fenol component (shogaol and gingerol) that there are in ginger oleoreesin can personate natural antioxidant. Natural antioxidant in the ginger oleoresin have potency to increase functional value of VCO as health oil.Method performed in this research are ginger oleoresin extraction and then enhancing to VCO then measured antioxidant activity with DPPH. VCO with addition of ginger oleoresin equal to 1% taken a fancy by panelist and do not significant with control (without addition of ginger oleoresin). But that way, addition of oleoresin manifestly can improve panelist preference to VCO aroma. VCO that added ginger oleoresin with higher level concentration (2, 3 and 4%) exactly less taken a fancy by panelist as a whole. That thing is related to degradation mount hobby of panelist at clearness, color and flavor VCO effect of increasing ginger oleoresin concentration at VCO. Addition of ginger oleoresin at VCO had significant an effect of antioxidant activity test by using DPPH as free radical.